Assessment of perceived distress due to nasopharyngeal swab collection in healthy Indian infants participating in a clinical trial. Issue 4 (26th December 2021) - Kawade, Anand; Dayma, Girish; Apte, Aditi; Roy, Sudipto; Gondhali, Arun; Juvekar, Sanjay; Bavdekar, Ashish
Abstract: Routinely children are exposed to various procedures as a part of clinical care and/or research participation. Public health strategies to contain current COVID‐19 pandemic demanded massive nasopharyngeal swab testing but limited data exist to confirm the extent of the pain and distress that result from this procedure. These data could help clinicians to formulate mitigation strategies, influence public health directives, and inform review boards/ethics committees to decide on risk‐benefit ratio of the procedure. Hence, an observational study to assess perceived distress was nested in a phase IV alternate and reduced dose schedule trial of the pneumococcal conjugate vaccine (PCV) in which nasopharyngeal swab (NPS) was used to collect nasopharyngeal secretions as part of the study procedure. Out of 805 infant participants enrolled in the main study, a total of 425 infants were enrolled and observed for procedural distress at 18 weeks and 10 months of age using the Face Leg Activity Cry and Consolability (FLACC) Scale. The FLACC score and duration of cry were recorded. The mean FLACC score changed substantially from preprocedural to procedure in both age groups (from 0.08 to 5.8 at 18 weeks and from 0.5 to 7.007 at 10 months. P = <.0001). The proportion of infants experiencing higher FLACC scores (7‐10) indicating severe distress increased significantly from 22% (n = 95) at 18 weeks to 61% (n = 248) at 10 months ( P < .0001). The mean duration of cry was significantly increased from 23.03 seconds at 18 weeks to 52.6 seconds at 10 months ( P = .00). Nasopharyngeal swab collection produced substantial distress which increased with age. Adequate training of sample collectors and supporting parent engagement during procedure could help in reducing the distress. Abstract : Nasopharyngeal swab collection in infants is distressful procedure. (a) The discomfort is more at 10 months of age as compared to 18 weeks. (b) It emphasizes the need for appropriate training, supports engagement of care takers, and use of alleviation measures. Findings of the study are important to pandemic context and could prompt the policy maker to think of pain/distress relieving measure to increase procedural compliance and public health behavior. These results could also help inform the review boards to decide on risk‐benefit ratio of the procedure while reviewing the trial protocols.